History learning with TikTok (HLTT) / Syaimak Ismail, Aemy Aziz and Muhammad Saiful Islam - Ismail, Syaimak; Aziz, Aemy; Ismail, Muhammad Saiful Islam (Universiti Teknologi MARA, Kedah, 2023)
History is not the favourite subject of the young generation today. History is considered an uninteresting subject and not necessary to learn. However, the subject of history remains a compulsory subject to be studied in all IPTA and IPTS in Malaysia, such as Malaysia Studies, Ethics and Civilization, and Ethnic Relations. In fact, students will not be able to graduate if they fail this subject. Accordingly, researchers look for solutions to assist students in improving their understanding of history. In this study, researchers use TikTok as a medium to teach history. The videos used are simple and easy to understand. The lecturer will share a short TikTok video that lasts 3 to 5 minutes after teaching a topic. The video includes a summary of the topic that was studied. This TikTok video's explanation assists students in better understanding history. The content of this TikTok is simple to understand due to the use of simple language, interesting writing, interesting visuals, and background music that students enjoy. This research uses a survey method to get students' answers on whether this medium of TikTok is suitable to be used to convey historical information or otherwise. The results of the study found that TikTok is a medium that is easy to understand and suitable for teaching and learning history. At the same time, through the medium of video, TikTok is able to focus on students and help them understand student content such as ethical history and civilization topics that are considered boring and uncritical. Therefore, teaching and learning through this TikTok video is able to add additional value to the delivery of lesson content and attract students to focus on the discussion topics that will be highlighted in class.